Quranpedia Website Development Using the Joint Application Development Method - Sarja Asra Winata; Eko Darwiyanto; Moch Arif Bijaksana (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
Quranpedia is a website built with codeigniter framework to facilitate muslims in searching for nouns and the verses containing the same nouns in the Quran by following structure of Wikipedia. The research employs the Joint Application Development in the process of developing the website and use black box testing to asses the functionality of the website according to the requirements. During the system requirements analysis process, Joint Application Development (JAD) relies on the active engagement of stakeholders to precisely capture users' viewpoints regarding business needs and collaboratively devise solutions. The extensive participation of stakeholders guarantees the effective representation of their opinions, fostering a collective effort in the development of solutions. To evaluate the website's functionality, black box testing is employed, and the results unequivocally demonstrate its high effectiveness in meeting all the specified criteria. The user-friendly interface, coupled with its comprehensive and responsive features, significantly enhances the process of studying the Quran, making it accessible to a wider audience. As Quranpedia continues to evolve and improve, it is expected to serve as an invaluable aid for the Muslim community in deepening their understanding of the sacred Al-Quran. By providing easy access to nouns and their associated verses, Quranpedia empowers users to explore the profound meanings and teachings within the Quran's verses, fostering a stronger connection to their faith and enriching their spiritual journeys.